2018
DOI: 10.3390/min8060231
|View full text |Cite
|
Sign up to set email alerts
|

Microcrack Evolution and Associated Deformation and Strength Properties of Sandstone Samples Subjected to Various Strain Rates

Abstract: The evolution of micro-cracks in rocks under different strain rates is of great importance for a better understanding of the mechanical properties of rocks under complex stress states. In the present study, a series of tests were carried out under various strain rates, ranging from creep tests to intermediate strain rate tests, so as to observe the evolution of micro-cracks in rock and to investigate the influence of the strain rate on the deformation and strength properties of rocks. Thin sections from rock s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The relative work indices (Wr) were also calculated with respect to to the ore with the lowest work index (i.e., work index of the ore divided by the work index of sulphide 1). The distribution of the copper mineral grains (bornite, chalcopyrite, malachite, and azurite) within the host rocks introduces structural defects which serve as sites for crack initiation and propagation upon the application of an external load on the particles during comminution (Charikinya, Bradshaw, and Becker, 2015;Chen, Xu, and Li, 2018;Fan et al, 2018;Germanovich et al, 1994;Ghorbani et al, 2013;Griffith, 1920;Shi, Zuo, and Manlapig, 2013;Viljoen et al, 2015;Zhao et al, 2016). The difference in the Wi values for the three copper ores can thus be attributed to mineral texture.…”
Section: Bond Work Index Brittleness and Toughnessmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative work indices (Wr) were also calculated with respect to to the ore with the lowest work index (i.e., work index of the ore divided by the work index of sulphide 1). The distribution of the copper mineral grains (bornite, chalcopyrite, malachite, and azurite) within the host rocks introduces structural defects which serve as sites for crack initiation and propagation upon the application of an external load on the particles during comminution (Charikinya, Bradshaw, and Becker, 2015;Chen, Xu, and Li, 2018;Fan et al, 2018;Germanovich et al, 1994;Ghorbani et al, 2013;Griffith, 1920;Shi, Zuo, and Manlapig, 2013;Viljoen et al, 2015;Zhao et al, 2016). The difference in the Wi values for the three copper ores can thus be attributed to mineral texture.…”
Section: Bond Work Index Brittleness and Toughnessmentioning
confidence: 99%
“…Ores are characterized by inhomogeneities such as flaws, joints, voids`, and a variety of minerals dispersed as grains of various sizes with differing interrelationships with one another, i.e. texture (Chen, Xu, and Li, 2018;Estay and Chiang, 2013;Fan et al, 2018;Hamdi, Stread, and Elmo, 2015;King, 2012;Zhao and Zhang, 2020;Zhou et al, 2015). These discontinuities influence the hardness and fracture toughness of rocks and, in turn, their fracture behaviour (Gutierrez and Youn, 2015), serving as stress risers where both crack initiation and propagation begin (Chen, Xu, and Li, 2018;Griffith, 1920;Zhao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As stress increases, the material may begin to collapse internally by creating microcracks that follow a fractal pattern. These microcracks continue to grow until they result in macroscopic failure that is also self-similar [9][10][11][12][13][14][15][16][17][18][19][20]. As microcracks grow, they release energy in the form of acoustic emissions and electromagnetic signals.…”
Section: Introductionmentioning
confidence: 99%
“…For Sanjome andesite, Young's modulus was shown to increase by 2% with a tenfold increase in the loading rate; meanwhile, Young's moduli of marble, granite, and sandstone decreased slightly with an increasing loading rate [15]. Only a few studies have explained the microcrack evolution, associated deformation, and strength properties of rocks with various strain rates [16]. Xu and Dai [17] showed that Young's and shear moduli exhibited some loading-path dependency under quasistatic loading but were insensitive to the loading path at high loading rates.…”
Section: Introductionmentioning
confidence: 99%